Revisiting the Nabucco Debacle: Myths and Realities. Issue 1 (2nd January 2018) - Skalamera, Morena
Abstract : The Nabucco pipeline has been the largest and, arguably, the most ambitious project promoted to "wean Europe from the Russian gas stranglehold." Both the EU and the United States were strong proponents of the plan. Meanwhile, Gazprom launched its giant South Stream project in strategic partnership with some of the most experienced European energy companies. Despite declarations by both Russia and the EU that Nabucco and South Stream were not competitors, they were designed to provide gas to the same sluggish southeastern European markets. At this writing both projects have been canceled. This paper provides an overview of the debate surrounding the Nabucco pipeline's cancellation. Conventional wisdom holds that Nabucco failed for political reasons, but the real cause of its failure was the emergence of two more economically viable pipeline plans.